2023
DOI: 10.47197/retos.v50.99398
|View full text |Cite
|
Sign up to set email alerts
|

Technology Readiness and Psychological Correlate with Academic Achievement of Elite Student-Athletes at the College Level?

Mochamad Ridwan,
Abdul Rachman Syam Tuasikal,
Fransisca Januarumi Marhaendra
et al.

Abstract: After the COVID-19 period, academic achievement among elite student-athletes has not shown any improvement and it is not yet known exactly the main factors that contributed to academic achievement. In addition, limited evidence in previous research that analyzed the relationship between technological and psychological readiness with academic achievement among elite student athletes at the college level became a gap in this study. Therefore, this study investigated the relationship between technological and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Data from scientific literature sources indicate that the success of athletes depends on four main aspects: physical, technical, tactical and psychological. At the same time, the psychological state of athletes during training and competition is fundamental to achieving better results (Akbar et al, 2024;Ridwan et al, 2023). The significant deviations of the communicative personality traits of the athletes of the experimental group from the standard parameters indicate some psychological deformation associated with incorrect attitudes and stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Data from scientific literature sources indicate that the success of athletes depends on four main aspects: physical, technical, tactical and psychological. At the same time, the psychological state of athletes during training and competition is fundamental to achieving better results (Akbar et al, 2024;Ridwan et al, 2023). The significant deviations of the communicative personality traits of the athletes of the experimental group from the standard parameters indicate some psychological deformation associated with incorrect attitudes and stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In the modern era, technology that has been used in sev-eral sectors such as physical education (Jastrow et al, 2022;Marín-Suelves et al, 2023;Ridwan et al, 2023;Zulkifli & Danis, 2022), health (Baashar et al, 2023;Kan Yeung et al, 2021;Rodríguez-Abad et al, 2021;Seals et al, 2021), busi-ness (Capasa et al, 2022;Rauschnabel et al, 2022), sports (Badau et al, 2023;Pu & Yang, 2022;Witte et al, 2022) encountered a significant increase in several countries. Data showed that using technology could provide benefit, which can help athletes to achieve their goals optimally (Jumareng et al, 2021;Jumareng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%